Pengembangan Instrumen Tes Pengetahuan Metakognitif pada Materi Pokok Asam Basa - Luawo, Aprilia Herman; Salempa, Pince; Ramlawati, Ramlawati (Program Pasca Sarjana UNM, 2021)
The objective of the study is to examine the quality of metacognitive knowledge test instrument on Acid-Base subject. The metacognitive knowledge is a deep awareness and understanding on the process and product of cognition possessed by the students. This study is a Research and Development (R&D) using Plomp’s development model which consisted of 5 stages, namely (1) initial investigation stage, (2) design stage, (3) realization stage, (4) test, evaluation, and revision stage, and (5) implementation stage. The test subject of the research was grade XI MIPA 1 at SMAN 1 Makassar with 33 students. The result of the content of questions validity based on the three experts confirmed as valid with CVI value 1 in very appropriate category. The test result of students’ response questionnaire is stated as meet the criteria because it indicates positive response by 77.78%. The analysis result of items validity is stated as valid category, rcount (Corrected Item Total Correlation) > rtable by 0.344; whereas, the items reliability is stated as reliable with the value of 0.827 which is in high category. The analysis of the average difficulty level of items is 0.61 with moderate criteria. The test instrument of distractor power shows good category with the average 0.44. The analysis result of the students’ metacognitive knowledge level obtains the average of good category by 66.47%.